Unravelling the evolution of Africa's drainage basins through a widespread freshwater fish, the African sharptooth catfish Clarias gariepinus. (19th April 2020) - Van Steenberge, Maarten W.; Vanhove, Maarten P. M.; Chocha Manda, Auguste; Larmuseau, Maarten H. D.; Swart, Belinda L.; Khang'Mate, Faustin; Arndt, Allan; Hellemans, Bart; Van Houdt, Jeroen; Micha, Jean‐Claude; Koblmüller, Stephan; Roodt‐Wilding, Rouvay; et al.
Abstract: Aim: The formation history of Africa's current river basins remains largely unknown. In order to date changes in landscape and climate, we studied the biogeography of the African freshwater fish with the largest natural distribution. We also validated biogeographical units. Location: Continental Africa. Taxon: Clarias gariepinus sl. Methods: We investigated mitochondrial cyt b sequences of 443 individuals from 97 localities, using a haplotype network and a genetic landscape analysis. We inferred a dated phylogeny using maximum likelihood and Bayesian inference approaches and reconstructed ancestral areas with S‐DEC and S‐DIVA models. Microsatellite genotyping complemented the mitochondrial approach in the Congo basin, where the latter revealed complex patterns. Results: Limited differentiation is found in northern and south‐western Africa, and sharp genetic differentiation in the continent's east and centre. Populations with affinities to neighbouring basins occur at the edges of the Congo province. High diversity exists in the south of the Congo basin. The Zambezi province is partitioned into eastern, central and western sectors. In the east, specimens were related to those from the Congo. In the west, they were similar to Southern representatives. Phylogenetic inference placed the origin of C. gariepinus in the East Coast, with intraspecific diversification starting around the Great Lakes. These events occurred ca. 4.8–1.65 and 2.3–0.8 MYA respectively. Main conclusions: Clades of C. gariepinus sl. show a clear geographical signature. The origin of C. gariepinus in the East Coast and diversification around the Great Lakes coincided with the periods of increased aridity. Low genetic differentiation in northern and southern Africa may result from connectivity during recent periods of higher rainfall. In contrast to other widespread African freshwater fish, colonization rather than extinction seemed to mediate distribution patterns. This can be explained by a high ecological tolerance. We highlight the species' suitability to study landscape and climate evolution at various scales.